(untitled) (Asian Education Studies, 2022)
Objective: To explore the feasibility and effect of mind map in PBL teaching of ophthalmology for five-year clinical medical undergraduates. Methods: Forty five-year clinical undergraduates who studied in the Second Clinical Medical College of Inner Mongolia University for Nationalities from February 2021 to July 2021 were randomly divided into PBL combined with mind mapping group and PBL teaching group. Among them, 20 medical students applied the combination of mind mapping and PBL teaching method, and the other 20 medical students applied PBL teaching method to learn the theoretical knowledge and practical teaching of ophthalmology. The differences between the two groups were compared through questionnaire feedback, theoretical examination, practical examination and medical record writing. Results: The experimental group was better than the control group in theoretical scores and clinical skills, and there was no statistical difference in medical record writing scores. The experimental group and the control group were superior to the control group in self-learning ability, learning efficiency, memory and understanding ability. There was no statistical difference between the experimental group and the control group in clinical skills, clinical thinking, problem-solving ability, learning interest, team cooperation ability, and doctor-patient communication. Conclusion: the application of mind map in five-year undergraduate clinical medical ophthalmology PBL teaching can significantly improve the five-year undergraduate medical students’ self-learning ability, learning efficiency, memory and understanding ability, which is worthy of promotion.